(untitled) (Bangladesh Journal of Anatomy, 2013)
Context: The jugular foramen is one of the most fascinating foramen present at the base of the skull attracting the imagination of many Anatomists worldwide as many important structures pass through it, and amongst them the intriguing structure is the internal jugular vein. The shape and size of the jugular foramen is related to the size of the internal jugular vein and the presence or absence of a prominent superior bulb. As most of the textbooks of Anatomy describe that the right jugular foramen is usually larger than the left jugular foramen. Henceforth the present study was undertaken in 55 skulls from the dept. of Anatomy. Measurements were taken with the help of sliding vernier caliper. Study type: Cross-sectional descriptive type. Place and period of study: Department of Anatomy, Rajshahi Medical College, Rajshahi and Pabna Medical College, Pabna from April 2010 to June 2011. Materials and Methods: Total fifty five (55) human adult skulls were collected from the Anatomy department of Rajshahi Medical College, Rajshahi and Pabna Medical College, Pabna at different times of the study period. The study was conducted to observe variations in the structure of the jugular foramen of the humans skull. Result: Out of 55 skulls (110 foramina) studied, the presence of dome indicating the presence of jugular bulb was found bilaterally in 100% of cases. 58.18% of cases showed that the size of right foramina were larger than the left foramina whereas 20% of cases showed that right foramina were equal to the left and in 21.82% of cases the left foramina were larger than the right side foramina. An important observation in the present study was the presence of either complete or partial septation in the jugular foramen. Conclusion: The findings of the study reveals that there are some differences among some parameters. The variations are might be due to the geographical variations of the skeletons. It needs further study with larger sample size from different geographical areas of Bangladesh. DOI: http://dx.doi.org/10.3329/bja.v10i2.17281 Bangladesh Journal of Anatomy, July 2012, Vol. 10 No. 2 pp 45-49